Morbidity and hospitalization costs of chronic diseases for the Unified National Health System - Soto, Pedro Henrique Teixeira; Raitz, Gabriela Martini; Bolsoni, Ludmila Lopes; Costa, Cássia Kely Favoretto; Yamaguchi, Mirian Ueda; Massuda, Ely Mitie (Rev Rene, 2015)
Objective: characterizing morbidity and hospitalization costs of chronic diseases (cardiovascular, respiratory, diabetes and cancer) for the Unified National Health System. Methods: a retrospective analytical study that used secondary data from the hospital information system of people aged ≥ 25 years. Results: among the four assessed morbidities, cancer and cardiovascular diseases have been the most prevalent. For cancer there was a predominance of females, aged between 45 and 49 years. Males had a higher incidence for cardiovascular diseases, with an age range of 55-59 years. These two diseases were the most costly for the system. The frequency of respiratory diseases follows a declining trend for both genders, while diabetes remained stable during the period. Conclusion: the highest prevalence of intervention was cancer among women and in men predominated cardiovascular diseases.